Estimation of shock index and need of blood transfusion in patients with post-partum hemorrhage: an observational study - Sirsam, Shyamkumar S.; Padole, Mrunal S.; Raut, Namita N.; Wahane, Aparna; Jawir, Gayatri M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Postpartum hemorrhage (PPH) is a leading cause of maternal morbidity and mortality worldwide, especially in low-resource settings. Early detection of hemodynamic instability is critical for timely intervention. The Shock Index (SI), defined as the ratio of heart rate to systolic blood pressure, may serve as a rapid bedside indicator to predict transfusion requirements in PPH. Methods: This prospective observational study included 120 women with PPH admitted to the Department of Obstetrics and Gynaecology, Government Medical College and Hospital, Akola, Maharashtra, from March 2023 to October 2024. Serial SI measurements at 30, 60 and 120 minutes postpartum were recorded and correlated with blood transfusion requirements, clinical interventions and outcomes. Data were analysed using SPSS version 16, with p<0.05 considered significant. Results: The mean SI peaked at 60 minutes (1.09±0.25). SI≥0.9 predicted transfusion need with 95% sensitivity and 60% specificity, SI≥1.1 predicted transfusion with 100% sensitivity and 93% specificity and SI≥1.3 predicted massive transfusion (>4 units) with an AUC of 0.97 (sensitivity 94%, specificity 98%). Cesarean deliveries had higher SI (1.26 vs. 0.99) and transfusion rates (88% vs. 56%) than vaginal births (p<0.001). Conclusions: Shock Index is a simple, non-invasive and reliable marker for early prediction of transfusion need in PPH. Incorporating SI thresholds (≥0.9 for vigilance, ≥1.1 for intervention, ≥1.3 for critical action) into PPH protocols can improve maternal outcomes.